Early growth responses of selected cucurbit vegetables to salt stress - Kareem, Noreen; Javed, Muhammad; Rashid, Madiha; Noreen, Zahra; Raees, Kakaish; Ilyas, Anam; Ashraf, Humira (International Journal of Applied and Experimental Biology, 2025)
This study investigated the early growth responses of selected highly economically cucurbit vegetables under varying salt concentrations. Four potential cucurbit species (Luffa aegyptiaca, Cucurbita pepo, Praecitrullus fistulosus, and Cucurbita maxima) were grown in Petri plates in a complete randomized block design with four replications. Varying salt solutions used were: 0, 50, 100, 150 and 200 mM of NaCl. Seed germination was monitored daily. Seedlings were harvested after 10 days and their shoot and root lengths, as well as fresh and dry weights were measured. The results showed that NaCl concentrations affected all measured parameters in all four vegetables. Germination percentage and germination index decreased under high salinity levels. Overall, germination and growth of the crops were better at 50 mM NaCl than those at the other salt levels. Of the four species, Cucurbita maxima had the highest germination percentage and germination index at all NaCl concentrations, indicating its superior tolerance to sat stress during germination stage. Cucurbita maxima was also superior to all species in terms of seedling biomass produced under varying levels of NaCl. Conversely, Cucurbita pepo showed the lowest germination percentage and index. The study concluded that Cucurbita maxima was the most tolerant species to salinity stress during the early growth stages.